2013
DOI: 10.1093/ndt/gft436
|View full text |Cite
|
Sign up to set email alerts
|

Children of non-Western origin with end-stage renal disease in the Netherlands, Belgium and a part of Germany have impaired health-related quality of life compared with Western children

Abstract: Children with ESRD of non-Western origin in three Western countries were found to be at risk for impaired HRQoL on emotional and school functioning. These children warrant special attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
0
13
0
2
Order By: Relevance
“…Educational attainment was categorized according to the highest successfully completed level of schooling: high level (high-level vocational training, “Hoger Beroeps Onderwijs,” “Fachhochschule,” or university) versus intermediate or low level. According to the definition of Statistics Netherlands [ 14 ], children were considered to be non-Western if they themselves or one or both parents had been born outside Western Europe.…”
Section: Methodsmentioning
confidence: 99%
“…Educational attainment was categorized according to the highest successfully completed level of schooling: high level (high-level vocational training, “Hoger Beroeps Onderwijs,” “Fachhochschule,” or university) versus intermediate or low level. According to the definition of Statistics Netherlands [ 14 ], children were considered to be non-Western if they themselves or one or both parents had been born outside Western Europe.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, they are vulnerable to a multitude of short- and long-term academic, behavioral, and negative emotional outcomes, such as withdrawn behavior. According to several studies conducted in both Europe and the USA, pediatric ESRD patients have significantly lower HRQoL scores compared with healthy children of the same age, especially concerning physical functioning in those treated by dialysis [1113, 29, 32, 35]. Furthermore, a study from the USA of 2500 pediatric patients from ten different physician-diagnosed disease clusters [36] found that patients with ESRD had significantly worse HRQoL scores compared to children with other chronic illnesses (including diabetes, cardiac conditions, asthma, and severe obesity) on the PedsQL 4.0 domains of physical health, psychological health, social functioning, and school functioning.…”
Section: Hrqol In Children With Esrdmentioning
confidence: 99%
“…A study conducted in children with ESRD in The Netherlands, Belgium, and part of Germany [35] found that children of non-Western origin were at risk for impaired HRQoL on emotional- and school-functioning domains. Also, low parental level of education may result in a decreased HRQoL in their children's childhood [61], and both patients and parents being part of nonintact households reported lower emotional HRQoL than those from married households [8].…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
“…[10][11][12] A study performed in the Netherlands and Belgium found that children, adolescents, and young adults of non-Western origin were more often treated with hemodialysis instead of peritoneal dialysis and had decreased access to kidney transplantation compared with children, adolescents, and young adults of Western origin. 13,14 However, although the total number of non-Western immigrants in Europe is growing, 15 information for other European countries is lacking. We therefore aimed to assess differences in: (1) access to kidney transplantation, (2) transplant survival, and (3) overall patient survival on RRT between racial groups among children, adolescents, and young adults on RRT in Europe.…”
mentioning
confidence: 99%